Calmodulin mutations affecting Gly114 impair binding to the NaV1.5 IQ-domain - Brohus, Malene; Busuioc, Ana-Octavia; Wimmer, Reinhard; Nyegaard, Mette; Overgaard, Michael Toft (Frontiers in Pharmacology, 2023)
Missense variants in CALM genes encoding the Ca 2+ -binding protein calmodulin (CaM) cause severe cardiac arrhythmias. The disease mechanisms have been attributed to dysregulation of RyR2, for Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT) and/or CaV1.2, for Long-QT Syndrome (LQTS).Recently, a novel CALM2 variant, G114R, was identified in a mother and two of her four children, all of whom died suddenly while asleep at a young age. The G114R variant impairs closure of CaV1.2 and RyR2, consistent with a CPVT and/or mild LQTS phenotype. However, the children carrying the CALM2 G114R variant displayed a phenotype commonly observed with variants in NaV1.5, i.e. Brugada Syndrome (BrS) or LQT3, where death while asleep is a common feature. We therefore hypothesized that the G114R variant specifically would interfere with NaV1.5 binding.Here, we demonstrate that CaM binding to the NaV1.5 IQ-domain is severely impaired for two CaM variants G114R and G114W. The impact was most severe at low and intermediate Ca 2+ concentrations (up to 4 µM) resulting in more than a 50-fold reduction in NaV1.5 binding affinity, and a smaller 1.5 to 11-fold reduction at high Ca2+ concentrations (25 to 400 µM) . In contrast, the arrhythmogenic CaM-N98S variant only induced a 1.5-fold reduction in NaV1.5 binding and only at 4 µM Ca2+. A nonarrhythmogenic I10T variant in CaM did not impair NaV1.5 IQ binding. These data suggest that CaM variants can perturb the cardiac sodium current, INa, and that the phenotypic spectrum of calmodulinopathies may likely expand to include BrS-and/or LQT3-like traits.